Effect of water temperature on the anesthetic effects of alfaxalone in carp (Cyprinus carpio) (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: To evaluate the effect of water temperature on intramuscular injected alfaxalone anesthesia in carp (Cyprinus carpio). Materials and Methods: Six healthy adult carp (C. carpio) were intramuscularly injected with alfaxalone (2.5, 5.0, or 7.5 mg/kg) at normal water temperature (25°C) and at low water temperature (2.5 mg/kg, 15°C). The respiratory rate, heart rate (HR), and anesthesia depth (AD) were evaluated every 5 min for 30 min after administration and every 1 h after 60 min after injection. Results: The respiratory and HRs did not change significantly upon alfaxalone injection, regardless of dose. However, a dose-dependent increase in AD scores was observed. Furthermore, 2.5 mg/ kg alfaxalone injected in 15°C water showed an almost equal anesthetic effect to that of 5.0 mg/ kg alfaxalone in 25°C water. Conclusion: Alfaxalone is readily available, and its anesthetic effect in carp was enhanced by lowering water temperature, illustrating the possibility of intramuscular injection of alfaxalone in fish.Adv. Vet. Anim. Res., 11(1): 27-32, March 2024http://doi.org/10.5455/javar.2024.k743